Fundamentals of algebra (second edition) - Hassan, Suraya; Alamin, Hamidah; Saidin, Nurhafizah; Hairom, Juhaidah; Mohd Bashah, Bahirah; Mat Zean, Hazaliza (Cengage Learning Asia Pte Ltd., 2022)
FUNDAMENTAL OF ALGEBRA (SECOND EDITION) is a comprehensive guideline on the subject of Pre-Calculus. This book is specially designed for upper secondary and matriculation students, in particular students taking Mathematics 1 (MAT0114) at the Centre for Foundation Studies, IIUM (CFSIIUM). This book is prepared by experienced instructors based on the latest syllabus, tailored to suit the needs of students in preparing for the end of semester examinations.